Leveraging live e-commerce to enhance online repurchase intentions for luxury brands: Evidence from tiktok in China - Zhang, Tianyang; Lee, Khai Loon; Puteri Fadzline, Muhamad Tamyez (Global Academic Excellence (M) Sdn. Bhd., 2024)
This study explores the impact of live e-commerce on enhancing online repurchase intentions for luxury brands, focusing on TikTok in the Chinese market. Drawing on theoretical frameworks in consumer behaviour and digital marketing, the research investigates the interplay between live e-commerce features, brand attitudes, and purchase motivations. Data were collected through a mixed-methods approach, including surveys of TikTok users and case studies of luxury brand campaigns. The findings highlight that interactive elements, real-time engagement, and influencer credibility significantly influence consumer trust and satisfaction, driving repurchase intentions. Moreover, the study identifies cultural nuances in the Chinese context that shape consumer perceptions of luxury and authenticity in live e-commerce. These insights provide practical implications for luxury brands aiming to optimize their digital strategies and build sustainable relationships with online consumers. This study contributes to the growing body of literature on digital commerce and offers a roadmap for leveraging live e-commerce to enhance brand loyalty and drive sales in competitive markets.